Calculation Thickness of the Added Flexural Layer on Composite Layer using a Light Weight Deflectometer (LWD) Pusjatan - Wijaya, Aldi Latna; Abdullah, Arif Chandra; Syafier, Siegfried; Yahya, Robby Gunawan (Universitas Negeri Padang, 2024)
Calculating the thickness of the flexible overlay needs to consider several factors, such as traffic load, soil characteristics, existing pavement conditions, and planned changes to the road design. This procedure generally uses recognized pavement design methods, such as the AASHTO 1993 method (Guide for Design of Pavement Structures). This research aims to determine the thickness of the added layer using an asphalt layer on composite roads in accordance with the 1993 AASHTO standards. It is hoped that this method can produce an effective overlay design, extend the life of the pavement, and increase the comfort and safety of road users. The data used in this research includes primary and secondary data. The results of this analysis are to calculate the STA 0 segment, for other STAs use the same method. From the Light Weight Deflectometer (LWD) deflection data, the Subgrade Reaction Modulus (k) value was 473 psi/in, the Concrete Elasticity Modulus (Ec) value was 4,843,105 psi and the Rupture Modulus (Sc') value was 699 psi. The traffic load used is 25.000.000, so the result of calculating the plate thickness to serve future traffic (Df) is 10.79 inches or 27.40 cm and the effective plate thickness value (Deff) is 9.13 inches or 23.30 cm, then the result is the added layer thickness (Dol) is 3.30 inches or 8.39 cm